2019
DOI: 10.1016/j.heliyon.2019.e02456
|View full text |Cite
|
Sign up to set email alerts
|

Projection the long-term ungauged rainfall using integrated Statistical Downscaling Model and Geographic Information System (SDSM-GIS) model

Abstract: An accuracy in the hydrological modelling will be affected when having limited data sources especially at ungauged areas. Due to this matter, it will not receiving any significant attention especially on the potential hydrologic extremes. Thus, the objective was to analyse the accuracy of the long-term projected rainfall at ungauged rainfall station using integrated Statistical Downscaling Model and Geographic Information System (SDSM-GIS) model. The SDSM was used as a climate agent to predict the changes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The evaluation results demonstrate that the SDSM model effectively simulates the mean and standard deviation components of precipitation, as well as minimum and maximum temperatures, closely aligning with the observational averages. These findings are consistent with the results of the study by Tukimat et al (2019). The simulated maximum and minimum temperatures show a better agreement with the observed values compared to the simulated precipitation.…”
Section: -1-evaluation Of Sdsm Performance In Simulating Rainfall And...supporting
confidence: 91%
“…The evaluation results demonstrate that the SDSM model effectively simulates the mean and standard deviation components of precipitation, as well as minimum and maximum temperatures, closely aligning with the observational averages. These findings are consistent with the results of the study by Tukimat et al (2019). The simulated maximum and minimum temperatures show a better agreement with the observed values compared to the simulated precipitation.…”
Section: -1-evaluation Of Sdsm Performance In Simulating Rainfall And...supporting
confidence: 91%
“…Meteorological factors came from daily monitoring data of the five national meteorological stations in and around the study area (available at http://www.resdc.cn/Default.aspx), and the values were converted into monthly averages. The ordinary kriging method (Tukimat et al, 2019) used in geographical spatial interpolation was adopted to calculate the rainfall amount, temperature and solar radiation in each catchment area, and the results are detailed in the Figs. S1eS6.…”
Section: Selection Of Environmental Variablesmentioning
confidence: 99%
“…Gulacha et al [17] assessed that the model and the observed showed a good ft in the Wami-Ruvu River Basin of Tanzania, and the SDSM's R 2 values between raw and model for temperature ranged from 0.42 to 0.98. Tukimat et al [18] found that the SDSM successfully provided long-term climate pattern at the gauged stations with an R value close to 1.0 in Kuantan River Basin of Malaysia. Dehghan et al [19] assessed that there is a good agreement between the simulated and the observed precipitation, and R 2 for precipitation is greater than 0.63.…”
Section: Introductionmentioning
confidence: 99%